Risk factors for avascular necrosis in patients with systemic lupus erythematosus: a multi-center cohort study of Chinese SLE Treatment and Research Group (CSTAR) Registry XXII - Cheng, Cheng; Huang, Can; Chen, Zhen; Zhan, Feng; Duan, Xinwang; Wang, Yongfu; Zhao, Cheng; Wu, Zhenbiao; Xu, Jian; Li, Hongbin; Yang, Min; Wu, Rui; et al. (Arthritis research & therapy, 2023)
Avascular necrosis is a common organ damage in SLE patients, which can influence patients' life quality. Conflicting results exist in risk factors of AVN in SLE patients. The aim of this study was to illustrate risk factors predicting the occurrence of avascular necrosis (AVN), also known as osteonecrosis, in systemic lupus erythematosus (SLE) patients in Chinese SLE Treatment and Research Group (CSTAR), a multi-center cohort of Chinese SLE patients. SLE patients in CSTAR without existing AVN at registration were included. At least two follow-ups and an observation period of no less than 2 years for AVN event were required. Univariate and multivariate Cox regression analyses were used to evaluate risk factors for AVN in SLE patients. Coefficient B was transformed to risk score for the development of a risk stratification model. One hundred six (2.59%) of 4091 SLE patients were diagnosed AVN during follow-ups of no less than 2 years. Multi-variate Cox regression analysis suggested that SLE onset age ≤ 30 (HR 1.616, p 0.023), arthritis (HR 1.642, p 0.018), existing organ damage (SDI ≥ 1) at registration (HR 2.610, p < 0.001), positive anti-RNP (HR 1.709, p 0.006), and high glucocorticoid maximum daily dose at registration (HR 1.747, p 0.02) were independent risk factors. A risk stratification system was developed according to the risk factors, and patients were divided into high risk (3-6) and low risk (0-2). The AUC of 0.692 indicated moderate discrimination. The calibration curve in internal validation was drawn. Patients with SLE onset age ≤ 30, arthritis, existing organ damage (SDI ≥ 1) at registration, positive anti-RNP, and high glucocorticoid maximum daily dose at registration are at high risk for AVN and require attention.